2002
DOI: 10.1111/j.1469-7793.2002.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine inhibition via A1 receptor of N-type Ca2+ current and peptide release from isolated neurohypophysial terminals of the rat

Abstract: The modulation by ATP of pre-synaptic ion channels (Zimmermann, 1994) via specific purinergic receptors, for example, could result in changes in subsequent release of neurotransmitters from the pre-synaptic site and, as a consequence, on the functional effect at the post-synaptic site.ATP is rapidly hydrolysed by ecto-nucleotidases (Gordon et al. 1989) even at pre-synaptic sites (Thirion et al. 1996) to adenosine 5‚-diphosphate (ADP), adenosine 5‚-monophosphate (AMP) and adenosine. Adenosine, the final hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Finally, a local regulation of ecto-ATPases in the neurohypophysis may increase adenosine concentration in the vicinity of the secretory terminals. It has been shown that adenosine can block calcium channels on nerve terminals and thus inhibit both VP and OT secretion (Wang et al, 2002). Thus, this could be another negative signal for VP secretion.…”
Section: Theoretical Model Of How Pituicytes May Modulate Neurohormonmentioning
confidence: 99%
“…Finally, a local regulation of ecto-ATPases in the neurohypophysis may increase adenosine concentration in the vicinity of the secretory terminals. It has been shown that adenosine can block calcium channels on nerve terminals and thus inhibit both VP and OT secretion (Wang et al, 2002). Thus, this could be another negative signal for VP secretion.…”
Section: Theoretical Model Of How Pituicytes May Modulate Neurohormonmentioning
confidence: 99%
“…J. Zhu et al, 2002) in the hippocampus, the primary mechanism underlying adenosineinduced synaptic depression is inhibition of calcium influx into presynaptic nerve terminals . In area CA1 of the hippocampus, as well as other areas, the adenosine A 1 receptor subtype decreases neurotransmitter release from presynaptic nerve terminals primarily by inhibiting N-type calcium channels (Mogul et al, 1993;Yawo and Chuhma, 1993;Mynlieff and Beam, 1994;Wu and Saggau, 1994;Ambrosio et al, 1997;Zhang and Schmidt, 1999;Brown and Dale, 2000;Park et al, 2001;Sun et al, 2002;Wang et al, 2002;Manita et al, 2004). Therefore, our study suggests that p38 MAPK activation is a necessary step for A 1 receptor activation to decrease synaptic transmission by decreasing presynaptic voltage-dependent calcium channel function.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it is thought either to be transported into the extracellular environment via bi-directional nucleoside transporters or to result from the breakdown of ATP by endonucleases. Both the synaptic cleft and the neurohypophysis contain endonucleases (Dunwiddie et al 1997;Wang et al 2002) and large amounts of ATP are found inside synaptic vesicles-both dense-core and small, clear vesicles. The abundance of spontaneous activity seen in this system suggests that breakdown of ATP accounts for a significant source of available adenosine.…”
Section: Sources Of Adenosinementioning
confidence: 99%
“…SON and PVN neurons can be spontaneously active both in vivo and in vitro, and several neurotransmitters not only modulate this activity (Armstrong 1995;Li and Hatton 1996;Shibuya et al 2000), but also control OT and VP release from the neurohypophysis (Sladek and Kapoor 2001;Wang et al 2002). Recordings from horizontal and coronal brain slices containing the SON show an abundance of postsynaptic potentials (PSPs), mediated largely via cation-fluxing glutamate receptors or GABA A receptors.…”
Section: Introductionmentioning
confidence: 99%